Mobile 2D platform historical game: God's commandments - Chang, Jia Zheng (2019)

(untitled)
This project is an historical educational game design based on bible’s god commandment. It will provide a mobile application environment for the users to learn god’s commandment. It will be demonstrated in the game levels associate with the commandments. Nowadays, people intend to use mobile application more compare to reading a bible because they find it bored. Thus, the youths do not know much about god’s commandment. The objective is to develop a 2d mobile platform historical game to attract the youths in order to deliver to them the knowledge of god’s commandment. The primary game design is in 2d platform which similar to the design of super bros Mario and granny smith. In short, the game require player controls a player model and go through tough obstacles, earn points, gain achievements after completion of one level and proceed to next level. The existing effort now is reality game like playing hula-hop and mobile applications that only permit user to read the commandments not application-based game. This is the first god’s commandment application-based game in a nut shell. The god’s commandment game exists now yet to have a place in mobile application platform or any web-based application platform. To summarize it, the god’s commandment needs to be developed in an attractive way in order to carry out the goal which is to let people know about god’s commandment.